Incorporation of the Transverse Thoracic Plane Block Into a Multimodal Early Extubation Protocol for Cardiac Surgical Patients. (December 2021) - Cardinale, Jeffrey P.; Latimer, Ryan; Curtis, Candace; Bukovskaya, Yana; Kosarek, Logan; Falterman, Jason; Tatum, Danielle M.; Trusheim, Jay
Background: The aim for early extubation remains an important goal in cardiac surgical patients. Therefore, employment of a multimodal approach to pain management that includes a transverse thoracic plane block was retrospectively examined at a single-center tertiary care hospital on the effects of time to extubation, opioid consumption, and length of stay in patients undergoing cardiac surgery via median sternotomy. Methods: Blocks were performed on all cardiac surgical patients except for those undergoing left ventricular assist device placement, thoracic transplant, emergent surgery, or redo sternotomy. Following additional exclusions for intra- and postoperative complications unrelated to anesthesia, final analysis was conducted on 75 patients per group. Multimodal pain management included intravenous analgesics and transverse thoracic plane block where patients received 15 mL 0.5% bupivacaine + epinephrine bilaterally under ultrasound guidance prior to incision. Results: Following transverse thoracic plane block and multimodal analgesics, 50.6% of patients were extubated in the operation room versus 8.6% in the control group. Intraoperative opioids were decreased, and intensive care unit and total length of stay were reduced by 5 hours and 1 day, respectively, in block patients as compared with controls. Postoperative opioids were not significantly different. There were no reported complications directly attributed to the block. Conclusions: The transverse thoracic plane block and multimodal regimen for patients undergoing median sternotomy resulted in a significant number of patients extubated in the operation room without an increase in postoperative re-intubations. Moreover, the block appears to be a quick and safe procedure to utilize on cardiac surgery patients.